A point-estimate based method for soil amplification estimation using high resolution model under uncertainty of stratum boundary geometry. Issue 121 (June 2019) - Iiyama, Kahori; Yoshiyuki, Atsushi; Fujita, Kohei; Ichimura, Tsuyoshi; Morikawa, Hitoshi; Hori, Muneo
Abstract: This study provides a practical technique for stochastically estimating soil amplification under uncertainty of the geometry of stratum boundary. To evaluate the possible values of the non-linear soil response under ambiguity, a nonlinear dynamic analysis with a high resolution 3D-FEM model is preferable, although the computations still represent a rigorous task. This study modifies Rosenblueth's point estimate method (PEM), which is greatly advantageous from the viewpoint of computational time, and demonstrates that the proposed method can provide good estimations with a very small number of calculations compared to the Monte-Carlo method. To evaluate the ground response stochastically, the preferable probability density function (PDF) is also examined. Furthermore, the estimation accuracy of the exceedance probability and the limitations of the proposed method are also discussed. Abstract : Highlights: This paper provides a technique to estimate soil amplification under uncertainty of the geometry of stratum boundary. The proposed technique deals with such a very high-resolution 3D-FEM model as 704, 699 * 3 DOF to estimate ground strains. The technique consists of the high-speed calculation technique and the modified point estimate method (modPEM). The modPEM obtains the better estimation accuracy with the same computational cost as the conventional one. The proposed technique provides a reliable response estimation with 1/40 the computation effort for Monte Carlo simulation.